Cover Image, Volume 87, Issue 12. Issue 12 (11th November 2019) - Kryshtafovych, Andriy; Schwede, Torsten; Topf, Maya; Fidelis, Krzysztof; Moult, John
Abstract : Reverse Cover: The cover image is based on the Review Critical assessment of methods of protein structure prediction (CASP)‐Round XIII by Andriy Kryshtafovych, Torsten Schwede, Maya Topf, Krzysztof Fidelis, John Moult, DOI 10.1002/prot.25823 . An example of successful modeling of a 354 residue domain of a free modeling target T0969, ESKIMO1, a probable xylan acetyltransferase. Most of the structure core is modeled to a Cα accuracy of better than 1 (cyan) or 2 Angstroms (green). Target is shown in the left panel, and the most accurate CASP model in the right panel.